Pengaruh Fluktuasi Harga Minyak Kelapa Sawit terhadap Alokasi Tenaga Kerja dan Pendapatan Usahatani Kelapa Sawit Swadaya di Kabupaten Musi Rawas - Lifianthi, Lifianthi; Rosana, Elly; Thirtawati, Thirtawati (Seminar Nasional Lahan Suboptimal, 2024)
Lifianthi, L., Rosana, E., & Thirtawati, T. (2024). The Effects of Palm Oil Price Fluctuations on Farm Labor Allocation and The Income of Independent Smallholder Oil Palm Plantation in Musi Rawas Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 293–304).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Independent oil palm plantations are farms that produce Fresh Fruit Bunches (FFB) owned by individuals without being tied to a company and are usually managed by family labor.  The oil palm commodity is one of the export-oriented plantation commodities, and its price is highly dependent on the price in the global market.  The fluctuating condition of FFB prices greatly affects the allocation of labor and income of independent oil palm farmers. This study aimed to analyze the labor allocation of independent oil palm farmers, calculate the income of independent oil palm farmers, and analyze the effect of family labor allocation on the household income of independent oil palm farmers.  The research was conducted in two sub-districts, namely Suka Karya and Megang Sakti sub-districts in Musirawas Regency.  A survey research method with simple random sampling was carried out for 100 independent smallholder respondents. Calculation of research data with two conditions for each per 6 months, namely before and after the change in FFB price.  The results of the study for the average labor allocation before the price change was 117.40 mandays, while after that was 115.07 mandays, the average income before the price change was Rp29.280.176,- and after that was Rp25.764.662, -.  Regression analysis results for the effect of labor allocation on income before price changes obtained a coefficient value of 11270,54, while after, a the value was -4584,11.